Studies on Physico-chemical Properties, Fatty Acid Composition of Terebinth (Pistacia terebinthus L.) Oil and Presence of Aflatoxins in Fruits - Gecgel, Umit; Arici, Muhammet (Asian Journal of Chemistry, 2010)
In present study, physico-chemical characteristics, fatty acids composition and aflatoxin contents quantities of terebinth nuts (Pistacia terebinthus L.) were determined. Oil contents, free fatty acid contents, peroxide values, iodine values and fatty acids composition of oils extracted from ripe fruits were determined. It is suggested that on account of high oil contents (35.26-47.52 %), low peroxide values (0.45- 0.76 meqO2/kg) and nice aroma and taste of terebinth fruits they could possibility be used for the oil industry. Palmitic acid was the main saturated fatty acid (19.91-23.58 %) while oleic acid was the main mono-unsaturated fatty acid (49.26-52.67 %); and finally total trans fatty acids were found (0.16-0.89 %).